Organic fertilizer in combination with zeolite enhanced maize yield with lower greenhouse gas emissions in sandy loam soil in North China - Wang, Xuexia; Wang, Jiachen; Yan, Peirui; Zuo, Qiang; Sun, Qinping; Liu, Dongsheng (Frontiers in Sustainable Food Systems, 2025)
IntroductionThere is limited knowledge about how co-applying organic fertilizer and zeolite influences maize yield and soil greenhouse gas (GHG) emissions in sandy loam soil.MethodsIn the present study, a 3-year maize field experiment was conducted on a sandy loam soil in the North China Plain with five treatments: no added fertilizer (control, CK), synthetic fertilizer (SF), organic fertilizer replacing 30% synthetic N fertilizer (OF), synthetic fertilizer with zeolite (ZSF), and organic fertilizer with zeolite (ZOF).ResultsResults showed that, compared with the SF treatment, the ZOF treatment significantly increased yield by 14.72–23.61% in each of the 3 years, ZSF by 13.91–15.59% in 2022 and 2023, and OF by 16.92% in 2023. Compared with ZSF, the cumulative CO2 emission was significantly increased by 4.52% in OF in 2023. Compared with SF, the average N2O emission flux and cumulative (over 2022 and 2023) N2O emissions were significantly reduced by 6.74–8.23% and 6.10–8.79% by OF, 9.29–11.86% and 9.23–10.85% by ZSF, and 7.59–11.24% and 12.27–16.06% by ZOF, respectively. Compared with SF, the total global warming potential (GWP) was significantly lower by 4.78% in ZOF in 2023, the greenhouse gas intensity (GHGI) was significantly lower over the 3 years of trials by 6.45–15.31% and 14.16–21.06% in treatments ZSF and ZOF, respectively, and was significantly lower by 10.53–13.13% in OF in 2022 and 2023. Compared with SF, the levels of available potassium and phosphorus content, dissolved organic carbon content, soil β-glucosidase activity, and microbial biomass carbon and nitrogen concentration in the ZOF treatment were significantly higher by 7.34, 8.90, 19.48, 9.20, 8.42, and 11.29%, respectively; however, soil NH4+-N and NO3−-N were significantly lower by 9.08 and 9.30%, respectively. The beneficial yield effects were due mainly to the enhanced synchronization of nutrient availability, soil moisture, and microbial biomass, while the mitigation of N2O emission was mainly attributed to the decreasing soil NO3− and NH4+ concentrations in response to ZOF.ConclusionApplying both organic fertilizer and zeolite achieved increased maize yield and positive environmental benefits. This strategy could be adopted to improve maize production, mitigate greenhouse effects caused by N2O emissions, and improve soil quality in sandy loam soils.